2005
DOI: 10.1002/ejoc.200500161
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral Catalyst Modifiers by Hydrosilylation of Cinchonidine and Their Application in the Hydrogenation of 1‐Phenylpropane‐1,2‐dione and Ethyl Pyruvate on a Supported Pt/Al2O3 Catalyst

Abstract: Four new chiral modifiers were synthesized in order to investigate the effect of distal modifier substitution in the hydrogenation of ethyl pyruvate and 1-phenylpropane-1,2-dione on a supported Pt/Al 2 O 3 catalyst. The chiral modifiers were prepared in good to moderate overall yields by Pt-catalyzed hydrosilylation of 9-O-TMS-protected cinchonidine with triethylsilane, triphenylsilane, bis(dimethylsilyl)ethane and (+)-(R)-methyl(1-naphthyl)phenylsilane followed by cleavage of the silyl ether protective group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Ligand acceleration is readily observed in homogeneous catalysis, and in enantioselective hydrogenation over heterogeneous catalysts is associated mainly with ethyl pyruvate (EP) hydrogenation over cinchonidine (CD)-modifier Pt catalysts (Orito reaction) [2], whereas for other reactants the reaction rate does not differ much in racemic and enantioselective reactions and sometimes even rate deceleration is observed [9]. It is worth emphasizing that recent publications also have reported a lack of rate acceleration and high ee in liquid-phase EP [3][4][5][6] and gas-phase methyl pyruvate [7] hydrogenations. These are important experimental observations, and a detailed understanding of them plays a very important role in the development of mechanistic models for asymmetric heterogeneous catalysis.…”
Section: Letter To the Editormentioning
confidence: 98%
See 1 more Smart Citation
“…Ligand acceleration is readily observed in homogeneous catalysis, and in enantioselective hydrogenation over heterogeneous catalysts is associated mainly with ethyl pyruvate (EP) hydrogenation over cinchonidine (CD)-modifier Pt catalysts (Orito reaction) [2], whereas for other reactants the reaction rate does not differ much in racemic and enantioselective reactions and sometimes even rate deceleration is observed [9]. It is worth emphasizing that recent publications also have reported a lack of rate acceleration and high ee in liquid-phase EP [3][4][5][6] and gas-phase methyl pyruvate [7] hydrogenations. These are important experimental observations, and a detailed understanding of them plays a very important role in the development of mechanistic models for asymmetric heterogeneous catalysis.…”
Section: Letter To the Editormentioning
confidence: 98%
“…The increased turnover rate over modified sites has been considered a key mechanistic feature of reactant-modifier interactions, supported by the experimentally observed correlation of modifier concentration, enantiomeric excess (ee), and reaction rate, as well as the up to 100-fold-higher hydrogenation rate in the presence of modifier. The increased turnover rate mechanism has been challenged by recent experimental observations [3][4][5][6][7][8], however. Ligand acceleration is readily observed in homogeneous catalysis, and in enantioselective hydrogenation over heterogeneous catalysts is associated mainly with ethyl pyruvate (EP) hydrogenation over cinchonidine (CD)-modifier Pt catalysts (Orito reaction) [2], whereas for other reactants the reaction rate does not differ much in racemic and enantioselective reactions and sometimes even rate deceleration is observed [9].…”
Section: Letter To the Editormentioning
confidence: 99%
“…[163][164][165][166][167] A broad range of alkaloids and derivatives, 153,[168][169][170][171][172][173][174][175][176][177][178][179][180] various chiral amines, 146,181-184 amino alcohols, [185][186][187][188][189][190] amides and amino-phenols, 191 alcohols and diols, 191,192 amino acids and derivatives, 191,193,194 hydroxyacids, 77 and organotin compounds 151,195,196 have been tested to extend the circle of useful catalysts. Some outstanding synthetic modifiers are shown in Figure 10.…”
Section: R-functionalized (Activated) Ketonesmentioning
confidence: 99%
“…Analog tethering chemistry has already been used successfully in the making of stationary chiral phases for chromatographic applications [19,20], and preliminary work has been reported on the used of tethered cinchona to promote Michael addition reactions [21,22]. A couple of studies on similar systems have also been reported in the past which provide limited characterization information on the tethering chemistry [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%